Growth in floor area: the blind spot in cutting carbon [version 3; peer review: 3 approved] - David Ness (Emerald Publishing, 2020)
While most efforts to combat climate change are focussed on energy efficiency and substitution of fossil fuels, growth in the built environment remains largely unquestioned. Given the current climate emergency and increasing scarcity of global resources, it is imperative that we address this 'blind spot' by finding ways to support required services with less resource consumption. There is now long overdue recognition to greenhouse gas emissions 'embodied' in the production of building materials and construction, and its importance in reaching targets of net zero carbon by 2050. However, there is a widespread belief that we can continue to 'build big', provided we incorporate energy saving measures and select 'low carbon materials' − ignoring the fact that excessive volume and area of buildings may outweigh any carbon savings. This is especially the case with commercial real estate. As the inception and planning phases of projects offer most potential for reduction in both operational and embodied carbon, we must turn our attention to previously overlooked options such as 'build nothing' or 'build less'. This involves challenging the root cause of the need, exploring alternative approaches to meet desired outcomes, and maximising the use of existing assets. If new build is required, this should be designed for adaptability, with increased stewardship, so the building stock of the future will be a more valuable and useable resource. This points to the need for increased understanding and application of the principles of strategic asset management, hitherto largely ignored in sustainability circles, which emphasize a close alignment of assets with the services they support. Arguably, as the built environment consumes more material resources and energy than any other sector, its future configuration may be critical to the future of people and the planet. In this regard, this paper seeks to break new ground for deeper exploration.